Effectiveness of the 360 degree Appraisal : Employee's Perspective - Banga, Rachita (2015)
Measuring performance is imperative for the organisation and using the right form of appraisal critical. Performance appraisals can help in determining the strengths and weaknesses of employees. Numerous studies have been carried out of performance appraisal and the various methods that exist to measure performance. The main focus of this study is on the 360 degree feedback process which is now being implemented by many companies. This study attempts to understand the experiences of employees with the 360 degree appraisal process. The introduction and the literature review throws light on studies which have been conducted to show the benefits of 360 degree appraisal process for the companies. The in the literature review were then identified and it was found that there were no studies conducted on the benefits of the 360 degree from the point of view of employees. The present study explores the experiences of the consumers with this method of appraisal and whether they prefer this method over traditional performance appraisal. In order to achieve rich data, interviews were conducted with a total of 9 participants. The data collected from the interviews were then analysed with the help pf thematic analysis (Braun and Clarke, 2006). The findings of this study are presented with the help of excerpts from interviews collected. From the findings of the present study, it was clear that employees preferred 360 degree over traditional performance appraisal. Since there are no studies on the perspectives of employees, it makes it very interesting to conduct a study on this topic.